Neural representation of three-dimensional acoustic space in the human temporal lobe - Zhang, Xiaolu; Zhang, Qingtian; Hu, Xiaolin; Zhang, Bo (Frontiers in Human Neuroscience, 2015)
Sound localization is an important function of the human brain, but the underlying cortical mechanisms remain unclear. In this study, we recorded auditory stimuli in three-dimensional space and then replayed the stimuli through earphones during functional magnetic resonance imaging. By employing a machine learning algorithm, we successfully decoded sound location from the blood oxygenation level-dependent signals in the temporal lobe. Analysis of the data revealed that different cortical patterns were evoked by sounds from different locations. Specifically, discrimination of sound location along the abscissa axis evoked robust responses in the left posterior superior temporal gyrus (STG) and right mid-STG, discrimination along the elevation axis evoked robust responses in the left posterior middle temporal lobe (MTL) and right STG, and discrimination along the ordinate axis evoked robust responses in the left mid-MTL and right mid-STG. These results support a distributed representation of acoustic space in human cortex.